MIDDLE CAMBRIAN ELDONIA FROM THE SIBERIAN PLATFORM - Friend D.; Zhuravlev A.Yu.; Solov'ev I.A. (My University, 2002)
The problematic fossil Eldonia ludwigi Walcott, 1911 is recorded first time in the Siberian Platform. It is discovered in the upper Middle Cambrian (Mayan Stage) of the southeastern slope of the Anabar Massif. The peculiarities of preservation allow us to reveal features in common with Ordovician-Devonian paropsonemids.
Keywords: Cambrian; Paleozoic::Cambrian; Палеозой::Кембрийская